2016
DOI: 10.1038/nrd.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of strategies to improve preclinical cardiac safety testing

Abstract: The early and efficient assessment of cardiac safety liabilities is essential to confidently advance novel drug candidates. This article discusses evolving mechanistically based preclinical strategies for detecting drug-induced electrophysiological and structural cardiotoxicity using in vitro human ion channel assays, human-based in silico reconstructions and human stem cell-derived cardiomyocytes. These strategies represent a paradigm shift from current approaches, which rely on simplistic in vitro assays tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
254
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(260 citation statements)
references
References 163 publications
4
254
0
2
Order By: Relevance
“…The resulting contractile and electrical dysfunction often leads to abnormal heartbeat and life‐threatening arrhythmias (Ewer and Ewer, 2015; Gintant et al , 2016). Arrhythmia is currently an immense burden on public health, with millions of people at risk of heart malfunction because of the cardiotoxic effects of drugs (Rubinstein and Camm, 2002; Vejpongsa and Yeh, 2014; Viskin et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting contractile and electrical dysfunction often leads to abnormal heartbeat and life‐threatening arrhythmias (Ewer and Ewer, 2015; Gintant et al , 2016). Arrhythmia is currently an immense burden on public health, with millions of people at risk of heart malfunction because of the cardiotoxic effects of drugs (Rubinstein and Camm, 2002; Vejpongsa and Yeh, 2014; Viskin et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We next assessed the effects of verapamil and paracetamol, which were found to have no effects on human ventricular repolarization, consistent with the known lack of proarrhythmic risk posed by these drugs (Gintant, Sager, & Stockbridge, 2016;Lawrence, Bridgland-Taylor, Pollard, Hammond, & Valentin, 2006;Redfern et al, 2003). Our APD data from healthy donor hearts showed that while paracetamol caused no change in APD (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, drug action as a function of pacing rate in the human heart warrants further assessment. Dofetilide, d,l-sotalol and quinidine have been associated with pro-arrhythmic risk (Frommeyer & Eckardt, 2016;Gintant, Sager, & Stockbridge, 2016;Redfern et al, 2003). Human trabeculae yielded information about the ability of dofetilide (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Contractility is a major pre-clinical and clinical parameter to assess normal and deficient contractile performance of the heart [46]. The RLFI system was thus evaluated as a platform to detect drug-induced effects on contractility.…”
Section: Evaluation Of the Inotropic Effects Of Blebbistatinmentioning
confidence: 99%